The Expression Profile, Clinical Application and Potential Tumor Suppressing Mechanism of hsa_circ_0001675 in Head and Neck Carcinoma - Cao, Yujie; Ye, Dong; Shen, Zhisen; Li, Zan; Li, Qun; Rong, Hao (Frontiers in Oncology, 2022)
Purpose: To identify circular RNA (circRNA) that may participate in the regulation of head and neck cancer (HNC), analyze its clinical application and predict the molecular mechanisms in HNC. Materials and methods: High-throughput sequencing was used to analyze the expression of circRNAs in 18 matched HNC tissues and adjacent normal tissues, and target circRNAs with significant differential expression were obtained. In 103 cases of HNC tissues and adjacent normal tissues, real-time fluorescent quantitative PCR (qRT-PCR) was used to verify the differential expression of target circRNAs, which was then combined with clinicopathological factors to analyze their potential diagnostic value. Bioinformatics were used to explore target circRNAs that act as competitive endogenous RNA (ceRNA) to construct a circRNA-miRNA-mRNA ceRNA regulatory network. The expression of mRNA was verified by immunohistochemistry (IHC). Results: A total of 714 differentially expressed circRNAs were detected in HNC, and the low expression of hsa_circ_0001675 was particularly significant (fold change [FC] = -4.85, P = 6.305E-05). Compared with normal tissues, hsa_circ_0001675 had significantly lower expression in HNC tissues (P < 0.05). Low hsa_circ_0001675 expression was positively related to tumor invasion and clinical staging (P < 0.05). The area under the ROC curve (AUC) of hsa_circ_0001675 is 0.7776. Low hsa_circ_0001675 expression was correlated with the overall survival rate of HNC patients (95% confidence interval = 0.7151–0.8402, P < 0.001). Bioinformatics constructed a ceRNA network of hsa_circ_0001675 with 6 differentially expressed miRNAs (hsa-miR-330-5p, hsa-miR-498, hsa-miR-532-3p, hsa-miR-577, hsa-miR-1248, and hsa-miR-1305) and 411 differentially expressed mRNAs and found that the network functions were mainly enriched in Neuroactive ligand-receptor interaction, and the cAMP and calcium signaling pathways. Further bioinformatics predicted that miR577/TESC may be the downstream signaling pathway of hsa_circ_0001675 as demonstrated by IHC experiment. Conclusion: We revealed that hsa_circ_0001675 is downregulated in HNC and could be an effective biomarker for HNC diagnosis. Additionally, hsa_circ_0001675 may has a potential ceRNA mechanism and suppress the progression of HNC via hsa_circ_0001675-miRNA-mRNA axis.